Settling the good land : governance and promotion in John Winthrop's New England (1620-1650) - Delahaye, Agnès (Early American history series, 2020)
"Settling the Good Land: Governance and Promotion in John Winthrop's New England (1620-1650) is the first institutional history of the Massachusetts Bay Company, cornerstone of early modern English colonisation in North America. Agnès Delahaye analyses settlement as a form of colonial innovation, to reveal the political significance of early New England sources, above and beyond religion. John Winthrop was not just a Puritan, but a settler governor who wrote the history of the expansion of his company as a record of successful and enduring policy. Delahaye argues that settlement, as the action and the experience of appropriating the land, is key to understanding the role played by Winthrop's writings in American historiography, before independence and in our times"--